PENGARUH SHIFT KERJA TERHADAP POTENSI KECELAKAAN KERJA PADA PT PLN NUSANTARA POWER UNIT PEMBANGKITAN PUNAGAYA KABUPATEN JENEPONTO - Rukmana, St. Hardianti Hardianti (Universitas Teuku Umar, 2024)
This study aims to evaluate the effect of work shifts on the potential for workplace accidents at PT PLN Nusantara Power Unit Pembangkitan Punagaya. Using a quantitative approach, this study involved all 58 employees working in a shift system as the population and sample. Through questionnaires, data were collected for analysis using descriptive methods, instrument testing, classical assumption tests, and simple linear regression analysis. The results of the analysis indicate that although work shifts have a positive effect on the potential for workplace accidents, this effect is statistically insignificant (with a significance value of 0.458 > 0.05). The coefficient of determination (R2) of 0.010 indicates that only 1% of the variation in the potential for workplace accidents can be explained by the work shift variable, while the remaining 99% is influenced by other factors. Thus, this study concludes that the work shift system at PT PLN Nusantara Power Unit Pembangkitan Punagaya is not statistically proven to increase the potential for workplace accidents.Keywords : Work Shift, Potential for Work Accidents, Work Safety